KAJIAN YURIDIS DEMOSI KARYAWAN TINGKAT MANAJERIAL YANG MEMPUNYAI HUBUNGAN KERJA BERDASARKAN PERJANJIAN KERJA WAKTU TERTENTU (PKWT) (Studi Putusan PHI NO. 146/Pdt.SUS-PHI/2016/PN.JktPst Jo Putusan Mahkamah Agung NO. 257 K/Pdt.SUS-PHI/2017) - Rudi Fahrudi; Markoni Markoni (Legal Standing : Jurnal Ilmu Hukum, 2022)
Human resources are an important element in the company's operations to achieve company goals. The relationship between the company and employees is established in an employment relationship, which is carried out after an employment agreement is established. In the working relationship there is a performance appraisal which is followed up with work placements in the form of promotions, transfers and demotions. This study uses a legal research method with a juridical-normative study pattern, while the problem approach is based on a statutory approach and a case study approach that has a focus based on systematic law. The research study found that Judex Facti's legal considerations that took refuge in paragraph (1) Article 1338 of the Civil Code had "dwarfed" and "castrated" the principle of freedom of contract which was noble, inconsistent and contrary to the juridical basis of Article 32, Article 55, paragraph (1) Article 61 UU no. 13/2003 concerning Manpower, and has ignored the company's actions that do not allow employees to attend attendance so that Judex Facti's legal considerations have been wrong in applying Article 168 of Law no. 13/2003 concerning Manpower.